Results of Coppicing, Pollarding and Pruning Experiments to Stimulate Strychnos Nux-vomica Fruit Production - Nicholson, J. W. (Indian Forester, 1937)
The yield of kuchila seed is proportionate to the size of the tree. (2) Coppicing or pollardlng trees reduces the size of the tree and causes a loss in seed produotlon which is never likely to be made up. Pruning has the same effect but to a lesser degree. (3) Copplcing very young trees may result ultimately in their acqulrIng crowns of fuller spread than if they were left to grow naturally, but trees tend to develop spreading crowns as soon as height growth starts falling off, artificial measures to promote crown spread are therefore not likely to be worthwhile, (4) The yield of seed from individual trees fluctuates remarkably from year to year. Drought or fire, especially the latter, cause a subsequent drop in yield.